Research on using resistant sensor to predict corrosion under insulation of carbon steel - Hoang Lam Hong,; Nguyen Van Trang,; Dinh Thi Duyen,; Le Thi Hong Lien,; Pham Thy San,; Bui Thi Van Anh, (Vietnam Journal of Science and Technology, 2024)
Corrosion under insulation (CUI) is very common and severely occurs in chemical/oil and gas industries, however, it is difficult to detect this corrosion by non-destructive testing (NDT) techniques. Carbon steel resistant sensors were used to determine CUI in this research. The output voltage values of the sensor were measured over time and from which the corrosion loss in sensor’s thickness was calculated. Carbon steel samples were exposed to the sensors under the same conditions for the same periods, and the corrosion loss of the samples was determined by weight loss. The results show that when the sensors were corroded within 10-20 % the corrosion loss of carbon steel samples is equivalent to that calculated from the output data of the sensors with a standard deviation of 6-24 %. These results demonstrate the high potential of resistance sensors in determining CUI and predicting damage of industrial components and pipes.